(untitled) (Annals of Medical Research, 2021)
Aim: Enterobius vermicularis (pinworm) is a parasitic nematode that infects humans and causes gastrointestinal symptoms mostly in children. This retrospective study aimed to analyze cellophane tape (CT) examination findings from a parasitology laboratory in Aydin, Turkey. Materials and Methods: The present study included the CT examination results in Aydin Adnan Menderes University, Faculty of Medicine, Parasitology Laboratory from January 2016 to October 2020. Perianal CT preparations were screened for the presence of pinworm eggs with direct microscopy. Changes in the frequency of E. vermicularis by years and according to gender were evaluated. Statistical analyses were performed with Pierson Chi-square test. Results: Pinworm eggs were detected in 436 (8.2%) of 5300 perianal CT preparations during the study period of time. There was a decrease in the frequency of parasite in the last two years (p<0.05). In addition, males were more infected with the parasite than females; 9.5% and 7.2%, respectively (p<0.05). The vast majority of infected cases (89%) were children. The average number of CT preparations, which sent to the parasitology laboratory, was lowest in 2020. Conclusion: Our findings indicated that E. vermicularis was still considered as a public health problem in Aydin, despite the decrease in the last two years. As the average age of positive case in our study was considered, we came to conclusion that children should be informed about the pinworm infection and personal hygiene habits. The decrease in the average number of examined CT samples in 2020 could be related with novel coronavirus disease (COVID-19) pandemic that discouraged people to admit to hospitals.